Cloning and expression of the glycoproteins of pichinde virus by vaccinia virus. - Wanas, Essam A. (University of Ottawa (Canada), 1993)
Pichinde virus (Pic), like the other arenaviruses, possesses two glycoproteins, GP1 and GP2, that are derived by proteolytic cleavage from a precursor molecule, GPC. Within the arenaviruses, GP1 is the most heterogeneous protein, and GP1 of Pic differs from that of the other arenaviruses in having twice as many potential N-linked glycosylation sites, most of which appear to be utilized. In order to examine the effects of this heavy glycosylation on Pic GP1 structure and inmunogenicity, GPC of Pic was cloned and expressed in vaccinia virus. The recombinant vaccinia (vvGPC) expresses authentic Pic GPC as demonstrated by immunoprecipitation with MAb and several polyclonal anti-Pic sera. GPC expressed in vaccinia is fully glycosylated as it comigrates with Pic GPC. At the same time, sequence analysis of cDNA shows both nucleotide and amino acid changes compared to published sequences for Pic GPC, indicating that variation in the same strain of this virus occurs as virus is passaged in separate laboratories. Experiments to assess the ability of Pic GPC expressed in vaccinia to elicit anti-Pic antibody show that rabbit anti-vvGPC detects authentic Pic GPC and GP1. Site-directed mutagenesis was employed to remove a potential N-linked glycosylation site (aa 181-183) in Pic GPC. Attempts were made to produce recombinant vaccinia, vvGPC-183, harbouring the mutant Pic GPC.
Keywords: Biology, Microbiology.